Properties and origins of infectious rhinovirus type 14 particles of different buoyant densities. - Gauntt, C J (1975)
Isopycnic centrifugation of rhinovirus type 14 (RV14), purified from infected HeLa or KB cell cultures, into CsCl gradients resolved two bands of infectious virus particles with buoyant density values of 1.409 +/- 0.007 (H virus) and 1.386 +/- 0.004 (L virus) g/ml. Only H virus was detected by incorporation of radiolabeled uridine into viral RNA, and H virus accounted for the majority of infectivity in gradients. H and L virus could not be differentiated by plaque morphology, extent of neutralization by RV14-specific antiserum, or particle size. Electron microscope studies showed that most L-virus particles were associated with an amorphous material. Treatment of L virus with proteolytic enzymes or rebanding L virus in CsCl gradients resulted in recovery of the majority of infectivity as H virus. Virus purified from cell-free fluids from infected HeLa or KB cell cultures banded only as H virus. HeLa cell cultures challenged with purified H virus and harvested at 3 h postinoculation for virus purification yielded only infectious H virus. Both H and L viruses were detected in cell cultures that had been challenged with purified H virus and harvested at 12 h postinoculation. The data suggest that H virus represents progeny virus, whereas L virus represents sequestered infectious virus particles which become associated with an amorphous material and do not enter into viral replicative processes.